Reliable molecular trace-detection based on flexible SERS substrate of graphene/Ag-nanoflowers/PMMA - Qiu, Hengwei; Wang, Minqiang; Jiang, Shouzhen; Zhang, Lin; Yang, Zhi; Li, Le; Li, Junjie; Cao, Minghui; Huang, Jin (Sensors and actuators. B, Chemical, 2017)
•First, the G/AgNFs/PMMA flexible substrate was fabricated by using a facilegraphene templated electroreduction method.•Second, the detection limit for R6G in-situ detectionby covering the G/AgNFs/PMMA flexible substrate can reach 10−14M.•Third, the G/AgNFs/PMMA flexible substrate can be used on real-world objects with any arbitrary morphology. Flexible substrate consisted of PMMA-supported monolayer graphene with sandwiched Ag-nanoflowers (G/AgNFs/PMMA) for ultrasensitive, reproducible, and stable surface-enhanced Raman scattering (SERS) detection is reported. Graphene templated micro-current-assisted chemical reduction method was employed to support AgNFs growth, and uniform-distribution AgNFs with all directions nanotips can generate tremendous enhancement factor and intensive hotspots. The minimum detectable concentration (i.e., detection limit) for rhodamine 6G (R6G) in-situ detection by covering this as-synthesized G/AgNFs/PMMA flexible substrate can be as low as 10−14M. Moreover, graphene can effectively stabilize the SERS signals and protect AgNFs from oxidation, endowing this flexible substrate a long-term stability with maximum intensity deviation lower than 10%, for the quantitative measurements from spot-to-spot or substrate-to-substrate. In order to trial its practical applications with various real-world surfaces, the in-situ SERS detection of phenylalanine@apple, adenosine aqueous solution and methylene-blue@fish was performed by covering this G/AgNFs/PMMA flexible substrate. Clear Raman peaks can be obtained for all the selected samples with concentration of 10−10M and, importantly, good linear relationship between Raman intensity and molecular concentration indicates the potential application of the G/AgNFs/PMMA flexible substrate in quantitative determination. Thus, this high-efficiency and low-cost flexible SERS substrate may provide a new way for the molecular trace-detection in food security and environmental protection.